An Ecological Systems Approach to Family Counselling - Friesen, John D. (Canadian Journal of Counselling and Psychotherapy, 2012)
In counselling, the unit of treatment may involve the individual, family, school and community. This article proposes an outline for a counselling model which combines individual and ecological approaches to assessment and intervention. The principles of general systems theory are presented, followed by an application of these principles to family assessment and intervention. Case examples are providedto further illustrate how the ecological systems model is translated into clinical practice.